Flora útil. Etnobotánica de Nicaragua / Alfredo Grijalva Pineda - Grijalva Pineda, Alfredo (2005)
Pinophyta (gymnospermae) cycadaceae (sagu-palm family) zamiaceae, pinaceae (familia de los pinefamily, cupressaceae, araucariaceae, taxadales, dicotiledóneas, magnoliophyta, magnolio sida, magnoliidae, magnoliales, laurales, piperales, aristolochiales, nymphaeales, ranunculales, papaverrales, hamamelidae, hamamelidales, urticales, juglandaceae (familia del nogal), miricales, fagales, caryophylidea, caryophyllales, poligonales, theales, malvares, lecythidales, nepenthales, violales, salicales, capparales, ericales, ebenales primulales, rosidae, rosales, fabales, proteales, haloragales, mytales, rhizophorales, santalales, celestrales, euphorbiales, ramnales, linales, polygalales, sapindales, gerianales, apiales, asteridae, gentianales, solanales.